An Evaluation study of Platelet Volume Indices (PVI) in Type-2 Diabetes Mellitus and its Micro and Macro Vascular Complications - Desai, Killol Nathubhai; Lakum, Nayana R (Annals of Pathology and Laboratory Medicine, 2018)
Background: The study was performed to analyse PVI such as mean platelet volume (MPV), platelet distribution width (PDW) and platelet-large cell ratio (P-LCR) that are useful for identifying large and haemostatically active platelets, which are risk factors for developing diabetes and its complication. Methods: Case–control study was conducted on 1026 Type 2 diabetics and 616 nondiabetics. Detailed clinical history regarding duration, hypertension and complications was taken. PVI was obtained using three part automated cell counter. Fasting blood glucose, hemoglobin A1C, lipid profile, creatinine were also obtained. Diabetics were further categorized into patients with complications and without complications. Result: MPV, PDW, P-LCR and platelet count were significantly increased in diabetic patients with complications as compared to diabetics without complications and nondiabetic group (P < 0.0001, < 0.0001, 0.0044, 0.023 respectively). We found statistically significant correlation between MPV and diabetic retinopathy (P < 0.0001), nephropathy (P = 0.04), neuropathy (P < 0.0001), coronary artery disease (P < 0.0001), diabetic foot (P = 0.005). PDW was statistically significantly increased in diabetic retinopathy (P < 0.0001), neuropathy (P < 0.0001), coronary artery disease (P < 0.0001), diabetic foot (P = 0.005). P-LCR was statistically significantly increased in diabetic retinopathy (P < 0.0001), neuropathy (P = 0.003), coronary artery disease (P < 0.0001), diabetic foot (P = 0.034). Conclusion: MPV, PDW and P-LCR are predictive biomarkers of diabetic vascular complications. They are more significant in microvascular complications than macrovascular complications.